UJI AKTIVITAS ANTIBAKTERI EKSTRAK METANOL DAUN BAWANG BATAK (Allium chinense G. Don) TERHADAP Streptococcus mutans DAN Bacillus cereus SEBAGAI BAKTERI GRAM POSITIF - Aliyah Fahmi (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2019)
Batak Onion (Allium chinense G. Don) is one of the species of Allium plant which is used as a flavor enhancer typical for North Sumatran Batak cuisine. In addition, the Batak onion is believed to be a health herbal remedy such as an antibacterial agent. This research aims to determine antibacterial activity of methanol extracts of Batak leeks (Allium Chinense G. Don) on Streptococcus mutans and Bacillus cereus as Positive Gram Bacteria.  The method  was the agar diffusion method. Methanol extracts of Batak leeks were diluted using Dimethyl sulphoxide (DMSO) with concentration variations (0.88, 1.66 and 2.5)%. DMSO also was used as negative blank. The research model was in Vitro experimental research model.  The results showed that methanol extract of Batak leek had antibacterial activity against S. mutans with inhibition zone diameter (5,10.5,12.7)mm and B. cereus with inhibition zone diameter (10,12.4 , 12.2)mm. The inhibition zone diameter (0) mm for the DMSO as negative blank.